Eurostat methodology applied to the characterization of rural and urban Brazilian spaces - Braga, Gustavo Basto; de Carvalho Fiúza, Ana Louise; Remoaldo, Paula Cristina (Bulletin of Geography. Socio-economic Series, 2018)
The Brazilian official statistics show that the country is mainly urban, while authors including Veiga (2002) and Miranda and Silva (2013) present a more rural Brazil. The absence of a uniform way to define the rural areas in Brazil has led to diffused data about rural Brazil’s size. Therefore, are Brazilian regions predominantly urban, rural or intermediate? This paper applies the rural definition methodologies from Eurostat/European Union to the municipalities of Brazil. The results show the predominance of the intermediary category in Brazilian territory, while the population mostly lives in urban areas. However, due to methodological characteristics, this paper reinforces the necessity of developing other methodologies which would be able to identify rurality and urbanity, considering socioeconomic dimensions.